Probiotic Effects of Bacillus spp. on the Growth and Survival of Postlarvae of Macrobrachium rosenbergii - Rinisha, K; Mujeeb Rahiman, K M; Beevi, M Razia; Thomas, A P; Mohamed Hatha, A. A (Fishery Technology, 2025)
Negative impact due to continued usage of antibiotics in aquaculture for growth promotion and disease control has necessitated research on alternative strategies such as development of probiotic strains, immunostimulants and vaccination. In this study, the probiotic effect of a Bacillus spp. on the growth and survival of postlarvae (PL) of Macrobrachium rosenbergii was studied. The Bacillus spp. under investigation was introduced in to the PL through culture tank water, feed and both. Changes in the bacterial load and flora, weight gain, percentage survival and changes in water quality parameters such as pH, dissolved oxygen, nitrite and ammonia were studied for a period of three months. There was no significant variation in the survival and weight gain of the PL of the experimental groups. However considerable improvement was noticed in the water quality parameters such as nitrite and ammonia concentration of the culture water in the experimental groups compared to the control group.